Toe-in and toe-out walking require different lower limb neuromuscular patterns in people with knee osteoarthritis. (25th July 2018) - Charlton, Jesse M.; Hatfield, Gillian L.; Guenette, Jordan A.; Hunt, Michael A.
Abstract: Toe-in and toe-out gait modification has received attention lately as a promising treatment for knee osteoarthritis due to its potential to improve knee joint loading and pain. However, the neuromuscular patterns associated with these walking styles are not well known, a factor that may influence knee joint load itself. Our aim was to conduct a thorough examination of the neuromuscular patterns associated with toe-in and toe-out walking in people with knee osteoarthritis. Fifteen participants were instructed to walk in four different foot rotations: 10° toe-in, 0°, as well as 10° and 20° toe-out. Nine surface electrodes were placed over lower extremity muscles and a variety of muscle activation parameters were examined. Peak and average medial hamstrings muscle activation was increased ( p = 0.001, p < 0.001) during toe-in walking compared to toe-out walking. As well, average lateral gastrocnemius muscle activation was higher ( p = 0.001) during toe-in walking compared to 20° toe-out. Medial thigh muscle co-contraction was higher ( p = 0.003) during toe-in walking compared to all other conditions, and medial to lateral gastrocnemius activation ratio was lower ( p = 0.032) during toe-in walking. These findings suggest potential overall increased joint loading with toe-in walking as a result of muscle co-contraction. Long-term assessment of these strategies is warranted.